The role of gender in linking external sources of knowledge and R&D intensity - Sara Amoroso; David B. Audretsch (European Commission, Joint Research Centre (JRC), 2020)
Scholars examining the effect of knowledge spillovers on R&D and innovation all agree on one thing-there is a strong relationship between the firm's R&D effort and knowledge spillover. The sign of this relationship depends, however, on many things, such as the type of spillovers (horizontal, vertical, or from other sources), the level of appropriability , the type of firm (e.g., age and sector), and the measurement of the spillover itself. A missing piece of evidence to this literature is the role of gender in the founding team of the firm. Our contribution is to fill this gap by explicitly analyzing the role played by gender in the founding team. Given that the relationship between a firm's R&D intensity and external knowledge spillovers is ultimately context-specific, we analyse the differences between male-owned and female-owned young entrepreneurial firms with respect to the influence that knowledge spillovers have on their R&D intensity.
Keywords: 330; Women entrepreneurs; absorptive capacity; knowledge intensive enterprise; spillovers; Europe